The Impact of New Media on the Formation of Public Opinion among Education Teachers in Sulaimani a study devided from a master`s thesis in the field of media studies - Karim, Saman Fariq Hama Karim Hama; Mirza, آ.م.د. ڕۆزە حەمەوەیس حەمەمیرزا Hama (Sulaimani Journal for Humanities, 2025)
This research, titled “The Influence of New Media on Public Opinion Formation Among Sulaymaniyah's education teachers: A Case Study on Salary Delays” is an attempt to investigate the role of new media in shaping public opinion among Sulaymaniyah's education teachers, particularly concerning the issue of delayed salaries.The objectives of the study aim to examine the impact of new media on the issue of salary delays and the ongoing boycott by Sulaymaniyah's education teachers and identify which types of media have the most influence in shaping public opinion. Methodology, The research employs a descriptive-analytical approach using field survey questionnaires. A representative sample of 404 Sulaymaniyah education teachers was selected through simple random sampling.Key Findings, New media tools in general, and the Facebook platform in particular, have played a significant role in shaping the public opinion of teachers regarding the issue of salary delays. A majority of teachers have been influenced by messages conveyed through these tools, and they believe that these platforms have had an impact on their decision to extend the boycott of teaching in the city of Sulaymaniyah over the period from 2015 to 2025. Most users of new media tools in this study were female. However, based on the results of the Wilcoxon test, the level of engagement with new media tools was significantly higher among male teachers compared to female teachers.
Keywords: new media; Public Opinion; Sulaymaniyahs education teachers; Salary Delays